Compact tri-band T-shaped frequency reconfigurable antenna for cognitive radio applications - Abdullah Ali Jabber; Raad H. Thaher (Institute of Advanced Engineering and Science, 2020)
This paper presents, new compact tri-band and broadband frequency reconfigurable antenna for cognitive radio applications. The proposed antenna consists of an Ultrawideband sensing antenna and reconfigurable communicating antenna at the same substrate. The sensing antenna is a UWB printed elliptical monopole antenna operates at frequency band from 2.72 to 23.8 GHz which can cover the entire UWB frequency band from 3.1 to 10.6 GHz and cover the broadband up to 20 GHz. The communicating antenna is a T-shaped frequency reconfigurable antenna operates on three bands of 7.925 GHz, 13.16 GHz, and 14.48 GHz under (S11≤-10 dB) with a fractional bandwidth of 14.55%, 6.2%, and 3.3% respectively. The proposed antenna used to operate in two modes one for cognitive radio applications to cover WiMAX, land, Fixed and Mobile satellite, Radar, and broadband applications. The frequency reconfigurability is obtained by using only one RF switch (PIN diode) for changing the operating frequency. The antenna overall dimensions are 42x30x1.6 mm3 printed on an FR-4 epoxy substrate with relative dielectric constant εr=4.3, loss tangent tan (δ)=0.002 and 50Ω microstrip line feed. The maximum obtained simulated gain is 8.5 dB at 13.16 GHz. The S11 is under -20 dB and coupling between the two antennas is less than -15 dB at the resonant frequencies.